2017
DOI: 10.1080/01612840.2017.1373175
|View full text |Cite
|
Sign up to set email alerts
|

Beck Depression Inventory-II: Factor Analyses with Three Groups of Midlife Women of African Descent in the Midwest, the South, and the U.S. Virgin Islands

Abstract: This research encompasses a factor analysis of the Beck Depression Inventory-II (BDI-II), which involves three groups of midlife women of African descent who reside in the Midwest, the South, and the U.S. Virgin Islands. The purpose of the study was to determine the factor structure of the BDI-II when administered to a sample of women aged 40–65 of African descent who reside in the three distinct geographical regions of the United States. A correlational, descriptive design was used, and 536 women of African d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…Differences in hypertension prevalence among African-American women, when compared to other racial-ethnic groups, are related to lower socioeconomic status, daily work-life hassles, unfair treatment in society (discrimination and racism), acute stressors, and the cumulative impact of stress over the life course (Dennis, Markey, Johnston, Vander Wal, & Artinian, 2008;Gary et al, 2018;Ogedegbe, 2008). Research has linked increased stress with early onset of menopause among African-American women (Gold et al, 2001;Wassertheil-Smoller et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences in hypertension prevalence among African-American women, when compared to other racial-ethnic groups, are related to lower socioeconomic status, daily work-life hassles, unfair treatment in society (discrimination and racism), acute stressors, and the cumulative impact of stress over the life course (Dennis, Markey, Johnston, Vander Wal, & Artinian, 2008;Gary et al, 2018;Ogedegbe, 2008). Research has linked increased stress with early onset of menopause among African-American women (Gold et al, 2001;Wassertheil-Smoller et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that life stressors were associated with depression, social support, menopausal symptoms, the number of chronic conditions, and perceived health status. Various types of stress have been empirically shown to produce detrimental effects on mental health and were linked to increased rates of depression (Gary et al, 2018;Whooley et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations